1965
DOI: 10.1111/j.1365-2621.1965.tb01793.x
|View full text |Cite
|
Sign up to set email alerts
|

Certain Physiological and Biochemical Changes in the Developing Tomato Fruit (Lycopersicon esculentum Mill.)

Abstract: SUMMARY The biosynthesis of nonvolatile compounds by tomato fruit parallels the growth rate of the fruit, regardless of varieties studied. Volatile reducing substances (VRS, mμ100 g), reducing sugars (percent), water‐soluble pectins (percent), and organic acids (mg/100 g) progressively increase in quantity with advancing maturity. Total titratable acidity (percent) and total pectic materials (percent) increased during the initial stages of maturation, but gradually decreased as the fruit ripened. Ascorbic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

1966
1966
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 4 publications
4
18
0
1
Order By: Relevance
“…It estimated that reducing sugar content was increased with the advancement of ripening of fruit. Fill ripen tomato contained the highest quantity of reducing sugar while the mature green tomato contained the lowest quantity at all time of observations (Table 4) alsoDalai et al [5] also observed similar result.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…It estimated that reducing sugar content was increased with the advancement of ripening of fruit. Fill ripen tomato contained the highest quantity of reducing sugar while the mature green tomato contained the lowest quantity at all time of observations (Table 4) alsoDalai et al [5] also observed similar result.…”
Section: Resultssupporting
confidence: 66%
“…Sugar content varied with the stage of harvesting. [5] found that reducing sugar (%) were about 2.4% (large green), 2.90% (breaker), 3.10% (pink), 3.45% (red) and 3.65% (red ripen) of fresh weight. At all temperatures, fruits soluble sugars concentration increased with storage duration.…”
Section: Introductionmentioning
confidence: 97%
“…Sugar content varies with maturity stage at harvest (Sinaga, ). Dalal, Salunkhe, Boe, and Olson () found that at the mature‐green, breaker, pink, red, and red‐ripe tomato ripening stages, reducing sugars accounted for about 2.4%, 2.90%, 3.10%, 3.45%, and 3.65% on a FW basis, respectively. Regardless of temperature, the level of soluble sugar showed an increasing trend during storage.…”
Section: Changes In Eating Quality‐related Attributesmentioning
confidence: 99%
“…. (Dalal et al, 1965) Sugars Cv. Rio Grande Peak at green to turning stage and then decrease as ripening proceeds (Sammi & Masud, 2007) Reducing sugars Sucrose…”
Section: Carotenoids (Lycopene and β-Carotene)mentioning
confidence: 99%
“…Several investigators reported an increase in ascorbic acid content with ripening with either a continuing rise or a slight fall (Dalal et al, 1965) during the final stages of ripening. Watada et al (1976) also reported AA content of mature green tomato fruit to be essentially the same as in fully ripened ones.…”
Section: Ascorbic Acidmentioning
confidence: 99%